2016
DOI: 10.1016/j.cmet.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Increased Melatonin Signaling Is a Risk Factor for Type 2 Diabetes

Abstract: Type 2 diabetes (T2D) is a global pandemic. Genome-wide association studies (GWASs) have identified >100 genetic variants associated with the disease, including a common variant in the melatonin receptor 1 b gene (MTNR1B). Here, we demonstrate increased MTNR1B expression in human islets from risk G-allele carriers, which likely leads to a reduction in insulin release, increasing T2D risk. Accordingly, in insulin-secreting cells, melatonin reduced cAMP levels, and MTNR1B overexpression exaggerated the inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
196
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(222 citation statements)
references
References 46 publications
7
196
1
3
Order By: Relevance
“…This increase in MT2 levels is proposed to heighten the insulin-inhibitory effect of melatonin. On the other hand, the same study confirmed that global deletion of the MT2 receptor in mice results in hyperinsulinaemia in response to glucose administration and reduced insulin sensitivity in the liver [165].…”
Section: Therapeutic Agentssupporting
confidence: 70%
See 3 more Smart Citations
“…This increase in MT2 levels is proposed to heighten the insulin-inhibitory effect of melatonin. On the other hand, the same study confirmed that global deletion of the MT2 receptor in mice results in hyperinsulinaemia in response to glucose administration and reduced insulin sensitivity in the liver [165].…”
Section: Therapeutic Agentssupporting
confidence: 70%
“…The adverse effects of excess melatonin signalling: the need for a personalised medicine approach One mechanism for these melatonin-induced negative effects in individuals with the MNTR1B risk allele was initially proposed by Lyssenko et al [106] and independently confirmed by others [165]. Tuomi and colleagues determined that overexpression of MNTR1B in carriers of the risk allele leads to elevated MT2 in pancreatic beta cells [165].…”
Section: Therapeutic Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following a publication stating that enhanced melatonin signalling increases the risk of type 2 diabetes [1], two commentaries had opposite views on the relevance of these data [2,3]. This question is crucial as melatonin is available over-the-counter as a dietary supplement for its anti-oxidant/anti-ageing effect, and/or to treat acute or chronic sleep problems.…”
Section: Introductionmentioning
confidence: 99%